A Highly Efficient Copper-Catalyzed Three-Component Synthesis of 4-Aminoquinazolines - Yang, Lei; Luo, Honghua; Sun, Yan; Shi, Zhenyu; Ni, Kaidong; Li, Fei; Chen, Dongyin (Synthesis, 2017)
A highly efficient copper-catalyzed one-pot protocol is developed for the synthesis of 4-aminoquinazolines from easily available 2-iodo- or 2-bromobenzimidamides, aldehydes, and sodium azide. This one-pot approach proceeds via consecutive copper-catalyzed SNAr substitution, reduction, cyclization, oxidation and tautomerization. The corresponding target products (26 examples) are obtained in 50–90% yield.
Keywords: copper; 2-halobenzimidamides; sodium azide; catalysis; 4-aminoquinazolines